2015
DOI: 10.3109/03008207.2015.1040878
|View full text |Cite
|
Sign up to set email alerts
|

High-magnitude mechanical strain inhibits the differentiation of bone-forming rat calvarial progenitor cells

Abstract: The differentiation of bone forming progenitor cells into bone nodule forming cells was inhibited by TF due to the decreased expression of bone formation related factors such as BMP-2, Runx2 and Msx2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…(18% elongations at 6 cycles/min) significantly inhibited bone nodule formation and reduced BMP-2, Runx2, and muscle segment homeobox 2 (Msx2) expression in rat calvarial cells (5). These findings suggest that optimal force enhances, while excessive force inhibits, bone formation.…”
Section: Effect Of Mechanical Strain-induced Pge 2 Production On Bonementioning
confidence: 79%
See 3 more Smart Citations
“…(18% elongations at 6 cycles/min) significantly inhibited bone nodule formation and reduced BMP-2, Runx2, and muscle segment homeobox 2 (Msx2) expression in rat calvarial cells (5). These findings suggest that optimal force enhances, while excessive force inhibits, bone formation.…”
Section: Effect Of Mechanical Strain-induced Pge 2 Production On Bonementioning
confidence: 79%
“…The procedures used for osteogenic cell isolation and culture were previously described by Fushiki et al (5) and Bellows et al (11).…”
Section: Rat Calvarial Cell Culture Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Numerous studies have shown that mechanical stimulation increases bone formation in modelling the skeleton, whereas reduced mechanical loading, as observed in patients subjected to prolonged immobilization or bed rest and in astronauts in a microgravity environment, results in reduced bone mass. [3][4][5][6] Impaired osteoblast proliferation is believed to play an important role in microgravity-induced bone loss. 7,8 The mechanisms by which microgravity exerts these detrimental effects on osteoblast proliferation remain unclear and merit further research.…”
Section: Introductionmentioning
confidence: 99%